Yāqūt al-sayr - Kharoṭī, ʻAbd al-Ḥaqq (Da Islāmī ʻUlūmo da Ṡerano Markaz, 1988)
Versified biography of Prophet Muḥammad, d. 632, caliphs, and noted companions by a 19th century religious scholar from Afghanistan.